Effective stakeholder management and communication (Assemble You, 2023)
Welcome to Audio Learning from Assemble You. Stakeholder Management is the process of maintaining the best possible relationships with the people who have the biggest impact on your work. This could be customers, investors, suppliers, and even governments. If you don't know how to manage your relationships with your stakeholders, you're going to find yourself in trouble. This track is aimed at professionals who are running a project that involves other people and who may need a little extra help with improving the relationships with their stakeholders. Learning Objectives Learn what stakeholders are Learn how to identify stakeholders Learn how to manage stakeholders Learn the best ways to communicate with stakeholders.